The Caatinga Orchestra: Acoustic indices track temporal changes in a seasonally dry tropical forest - Oliveira, Eliziane Garcia; Ribeiro, Milton Cezar [UNESP]; Roe, Paul; Sousa-Lima, Renata S. (Elsevier, 2021)
Advances in technologies for data acquisition, storage and analysis have boosted Acoustic Ecology studies, but protocols are still lacking. There is a need of more research to understand which methodologies can be applied to answer ecological questions in different environments with varying temporal and spatial dynamics. Tropical forests are generally more complex than temperate ones, both in terms of use of acoustic space and species diversity. The seasonally dry tropical forest (SDTF) in Brazil, known as Caatinga, is a threatened biome, with two marked seasons that shape vegetation and animal activity patterns. In this study, we investigate the applicability of passive acoustics in monitoring SDTF, describing the soundscape and tracking diel patterns and seasonal changes. Combining multiple indices, visualization through false colour spectrograms and clustering, we describe the acoustic activity of the main faunal groups that compose the biophonic orchestra in a SDTF area in the Northeast of Brazil. Distinct patterns were found between day – when birds and wind were the main sound sources – and night – with Orthopterans occupying a large frequency band. Other sound sources in the SDTF soundscape included cicada, rain, and anthropogenic influence such as domestic animals, cars and gunshots. Clustering of eleven acoustic indices was useful to distinguish sound patterns from several sources, especially in the dry season. Further investigation within each cluster showed specific relationships among selected indices and different sound sources. Birds were associated with Entropy of the Spectral Peaks (EPS) and Orthopterans also had a relationship with EPS, as well as with Entropy of Average Spectrum (EAS) and High Frequency Cover (HFC). Variation in diel values of these selected indices, as well as the number of samples included in each cluster category, were successfully used to describe the acoustic activity of Birds and Orthopterans and to track changes between rainy and dry seasons. A better understanding of the soundscape dynamics in a highly seasonal tropical environment was achieved by applying cheap and reliable novel methodologies to study biodiversity in geopolitical regions where funding for conservation initiatives is limited.
Keywords: Acoustic indices; Bioacoustics; Ecoacoustics; Seasonally dry tropical forest; Soundscape